A high FT3 level might protect bone mineral density among euthyroid type 2 diabetes mellitus patients - Jiamin Song; Wenxin Li; Guoyue Yuan; Dong Wang; Li Zhao (Endocrine Connections)
Objectives: This research was to investigate the relationship among thyroid function, sensitivity to thyroid hormone indices, and bone mineral density (BMD) in euthyroid individuals with type 2 diabetes mellitus (T2DM). Methods: A total of 536 euthyroid patients with T2DM were included. The subjects were measured for anthropometric parameters, biochemical indicators, and clinical characteristics. Their bone density was tested by dual-energy X-ray, and then they were classified according to their outcomes. Results: In comparison to the normal BMD group, the FT3 level was notably reduced in the low BMD groups (P < 0.05). The patients were sequentially assigned to tri-sectional quantiles according to FT3. Compared with tertile 1, patients in tertile 2 had a higher value of BMD. Spearman correlation analysis showed that the FT3 level was positively associated with BMD. After adjustment in multiple linear regression, FT3 level remained significantly related to decreased BMD. A significant independent association between FT3 and BMD was found by multiple logistic regression analysis after adjusting for potential confounding variables (OR = 0.187, P < 0.05). No significant relation was found between thyroid hormone indices and BMD. Conclusion: FT3 level was independently associated with BMD in euthyroid patients with T2DM. High-normal FT3 may be a protective factor for BMD.